Istiqāmah dalam Perspektif Hadis - Rahmi Damis (AL-Fikr, 2011)
Istiqamah is an attitude of consistency fo doing religious (Islamic) teaching. It’s a behavior of Faithful in obeying God’s commends from the beginning he or she declared to be a muslim until the end of their life. Based on that, this article tried to explain what is the essentilal meaning of istiqamah ? what is the epistemology of istiqamah? And what is axiology of istiqamah? For dealing with those problems, the article uses theological approach and Qur’anic exegesis in order tp get a comprehensive describing of istiqamah in the Qor’an. The article discovered that the man who strongly occupied the istiqamah, whether in understanding, saying or actiting, would have a God’s blessing. According to Hadis (Prophet’s saying), a muslim who implemented istiqamah consistently would bring him  to have a happiness in his life and hereafter.